The dimensions of the roots of the human permanent dentition as a guide to the selection of optimal orthodontic forces - Lee Brian (Sciendo, 2023)
The dimensions of the roots of the teeth are important in the assessment of orthodontic anchorage and to estimate the forces to be used during orthodontic tooth movement.